2023
DOI: 10.1007/s44281-023-00001-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sugar metabolism on the dialogue between arbuscular mycorrhizal fungi and plants

Abstract: Arbuscular mycorrhizal (AM) symbioses in plants are broadly significant because of their capacity to facilitate water and nutrient acquisition and thus, to promote vigorous growth and development among host plants. Many horticultural plants, especially citrus plants, are highly dependent on AM fungi. In return, AM fungi receive sugars and lipids from their host plants. The sugars (mainly sucrose) are transported from the aerial parts of host plants to the roots and thus, form a mycorrhizal carbon pool. In root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“… 5 , 6 Plants can modify their sugar pools to function as the source of carbon and energy, or they can use them as signals and possibly as potential priming agents to enhance immune responses. 7–9 A plant’s ability to produce secondary metabolites (via the shikimic acid pathway) and produce respiratory energy for safeguards, repair, and maintenance of plant structure and activity as well as DNA repair enzymes for UV-B protection relies on the accessibility of carbohydrates from storage and photosynthesis. 5 , 10 , 11 For instance, Staaij et al showed that increased UV-B radiation reduces the amount of carbohydrates that are allocated to the roots of grassland plants, thereby reducing the infection induced by arbuscular mycorrhizal fungi (AMF).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 , 6 Plants can modify their sugar pools to function as the source of carbon and energy, or they can use them as signals and possibly as potential priming agents to enhance immune responses. 7–9 A plant’s ability to produce secondary metabolites (via the shikimic acid pathway) and produce respiratory energy for safeguards, repair, and maintenance of plant structure and activity as well as DNA repair enzymes for UV-B protection relies on the accessibility of carbohydrates from storage and photosynthesis. 5 , 10 , 11 For instance, Staaij et al showed that increased UV-B radiation reduces the amount of carbohydrates that are allocated to the roots of grassland plants, thereby reducing the infection induced by arbuscular mycorrhizal fungi (AMF).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon allocation is moving photosynthetically fixed carbon – mostly in the form of sugars – from source organs to different sinks located all over the plant. 7 , 26 , 27 The role of carbon allocation in affecting rice plants’ resistance to M. oryzae is one facet of this intricate relationship that is currently being studied 28–33 ( Figure 1 ). Plants use a basic physiological process called carbon allocation to control how photosynthetically fixed carbon is distributed throughout their different tissues.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] On the Jos Plateau the sweet potato root tuber is an effective and economic source of energy and other nutrients, however the shelf-life of the root tuber is seriously hampered by decaying fungal activities which are encouraged by the root tubers moisture content and sugar concentration. 8,10 The root tubers become moister and sweeter in taste after harvest, high in moisture content ranging 62.58-64.34, dry matter is low; carbohydrate consist mainly of starch; less pectin, hemicellulose and cellulose. [11][12][13] Sweetness in the root tubers is due to the presence of endogenous sugars: sucrose, glucose, fructose at harvest and maltose formed through starch hydrolysis by amylase during storage or through heat treatment; raffinose, stachyose and verbascose were the other oligosaccharides assayed in the root tubers.…”
Section: Introductionmentioning
confidence: 99%